The Performance of the Regional Disaster Management Agency of North Maluku Province in Disaster Logistics Distribution Services in Central Halmahera Regency - La Suhu, Bakri; Radjak, Darwin Abd; Ibrahim, Abdul Halil Hi; Rahadi, M. Rizki (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
The purpose of this research is to understand and explain the performance of the BPBD of North Maluku Province in the logistics distribution service in Messa Village and Kotalo Village, East Weda District, Central Halmahera Regency. This research uses a qualitative descriptive method aimed at describing events or activities within an institution and then elaborating on the issues being studied through several relevant indicators. Data collection techniques through; observation, interviews, documentation, data analysis techniques through; data reduction, data presentation, and conclusion, drawing, or verification. Based on the research results; first, the productivity of the BPBD of North Maluku Province in the logistics distribution service in Messa and Kotalo Villages has not been effectively implemented due to limited resources, Second, the quality of service has not been optimally carried out because the distribution of logistics does not yet have SOPs that are by field conditions, and the logistics distribution in terms of timeliness is still not appropriate because it takes about 4 days to reach the disaster-affected location. Third, the responsiveness of the BPBD of North Maluku Province in the logistics distribution service process in Messa Village and Kotalo Village has been very good. The team from the BPBD of North Maluku Province consistently responds well to the needs of the disaster-affected community, and fourth, the accountability of the BPBD of North Maluku Province's performance has been carried out and accounted for by the regulations and is reported through SAKIP and LKIP.